Poznań School of Legal Theory - Kwiatkowski, Paweł; Dersley, Stephen; Smolak, Marek (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2020)
"This book grew out of the conviction that the original concepts of the Poznań School of Legal Theory are still perfectly suited for application in the era of moral pluralism and multicentric legal systems. Moreover, the legal-theoretical proposals put forward by the circle of Poznań legal theorists, and supported by firm methodological foundations, have not, by any means, lost their value. Although each of the authors tackles issues from different perspectives, there is a discernible unity in their approaches, expressed in the conviction that modest analysis makes more sense than ambitious analysis of the concept of law or the nature of law. The Poznań School has made several valuable contributions to contemporary legal theory: Its works have drawn from Polish philosophy of language and therefore embedded its theoretical and legal considerations in the Polish philosophical culture; it created an original model method which consists of considering ideal situations in which dependencies are not disturbed by the influence of other factors; and it treats the human being as a rational person, and thus as a cognizing subject and a rational agent"--